Astrometry of directly imaged exoplanets with optical interferometry - Lacour, Sylvestre (Comptes Rendus. Physique)
Optical interferometry has always been seen as a promising but difficult technique for astronomy. Until the year 2018, it was excrucially limited in sensitivity to magnitudes below 10. However, thanks to the advent of the GRAVITY instrument, fringe tracking and dual field interferometry made it possible to observe very faint target. This paper presents the different techniques used by optical interferometry to perform astrometry. It shows why dual field interferometry has become the key technique for faint companions. Taking the exemple of the HD 95086 b exoplanet, we show how dual field interferomtry can detect an exoplanet as faint as magnitude 19.5, and how its astrometry was extracted. Use this example this paper explains how and why an astrometric accuracy of 10 µas is possible, and describes the remaining biases that can hinder this measurement. Last, we conclude by presenting the orbital trajectory of 10 exoplanets in 4 systems, and conclude with the short and longer term perspectives of the technique.